Vitamin D deficiency in Saudi Arabians: A reality or simply hype: A meta-analysis (2008-2015) - Haneen Al-Alyani; Haifa A Al-Turki; Omar N Al-Essa; Fawaz M Alani; Mir Sadat-Ali (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND AND OBJECTIVE: The objective of this systematic review was to determine from published data the prevalence of Vitamin D deficiency in the Saudi population. METHODS: An extensive and meticulous search was conducted for studies published in MEDLINE, EMBASE the Cochrane Central Register of Controlled Trials and Cochrane Database of Systematic Reviews (2008"2015), and the Science Citation Index published data from the Annals of Saudi Medicine and Saudi Medical Journal with the key words: Vitamin D deficiency, insufficiency, and Saudi Arabians. The inclusion criterion was studies published during 2008 to 2015, and studies involving healthy individuals between the age of 18 and 80 years. Binary random- effect model was used to estimate pooled Vitamin D deficiency. Prevalence rates along with overall estimate were presented by forest plot. Heterogeneity test was used to assess the significance of heterogeneity among studies. RESULTS: The authors identified 26 potentially relevant articles, 16 of which met the inclusion criteria. A total of 20,787 patients were analyzed. Sixty-two percent (12,959) were females, and the rest were males. The overall Vitamin D deficiency was 63.5% (95% CI: 53.3, 73.7). CONCLUSIONS: The currently available literature on the Saudi Arabian population suggests that the Vitamin D deficiency is around 60% and not 100% as indicated in some studies. The relatively small number of studies on the population and the different modes of diagnostic methodology used make the issue of correct figures of Vitamin D deficiency contentious.